2021
DOI: 10.3389/fpsyt.2021.713686
|View full text |Cite
|
Sign up to set email alerts
|

An Effective and Safe Novel Treatment of Opioid Use Disorder: Unilateral Transcranial Photobiomodulation

Abstract: Background: The opioid epidemic is a global tragedy even with current treatments, and a novel, safe, and effective treatment would be welcomed. We report here our findings from our second randomized controlled trial to evaluate unilateral transcranial photobiomodulation as a treatment for opioid use disorder.Methods: We enrolled 39 participants with active opioid cravings at 2 sites, 19 received the active treatment which consisted of a 4-min twice weekly (every 3 or 4 days) application of a light-emitting dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…In subsequent studies we have used the CTHEV to guide a lateralized treatment using unilateral transcranial photobiomodulation (tPBM), near infrared mode in two double-blinded randomized controlled trials. 13 , 18 We have also reported that HEV, as assessed using lateralizing field glasses, predicted response to left-sided rTMS 12 , 19 and that CTHEV would likely work as well. The potential importance of guiding treatment based on HEV makes sense given the observation that individuals with more negative left hemisphere are as likely to have histories of MDD as individuals with more negative right hemisphere.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In subsequent studies we have used the CTHEV to guide a lateralized treatment using unilateral transcranial photobiomodulation (tPBM), near infrared mode in two double-blinded randomized controlled trials. 13 , 18 We have also reported that HEV, as assessed using lateralizing field glasses, predicted response to left-sided rTMS 12 , 19 and that CTHEV would likely work as well. The potential importance of guiding treatment based on HEV makes sense given the observation that individuals with more negative left hemisphere are as likely to have histories of MDD as individuals with more negative right hemisphere.…”
Section: Discussionmentioning
confidence: 85%
“…The evidence presented on the correlations of the CTHEV lends further support to the psychological hypothesis and therapeutic method articulated in Dual-Brain Psychology. 9 , 13 HEV is a more complex concept than established hypotheses which propose that the right hemisphere is superior for emotional processing or that the right hemisphere processes negative emotion or withdrawal emotions. The dual brain hypothesis suggests that each hemisphere is associated with broad mental processes or personalities that differ in health and maturity and at the side that is healthier is a trait for an individual but varies among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations